A novel domain suggests a ciliary function for ASPM, a brain size determining gene - Ponting, C (Oxford University Press, 2006)
The N-terminal domain of abnormal spindle-like microcephaly-associated protein (ASPM) is identified as a member of a novel family of ASH (ASPM, SPD-2, Hydin) domains. These domains are present in proteins associated with cilia, flagella, the centrosome and the Golgi complex, and in Hydin and OCRL whose deficiencies are associated with hydrocephalus and Lowe oculocerebrorenal syndrome, respectively. Genes encoding ASH domains thus represent good candidates for primary ciliary dyskinesias. ASPM has been proposed to function in neurogenesis and to be a major determinant of cerebral cortical size in humans. Support for this hypothesis stems from associations between mutations in ASPM and primary microcephaly, and from the rapid evolution of ASPM during recent hominid evolution. The identification of the ASH domain family instead indicates possible roles for ASPM in sperm flagellar or in ependymal cells' cilia. ASPM's rapid evolution may thus reflect selective pressures on ciliary function, rather than pressures on mitosis during neurogenesis.